Gender-Differentiated Comorbidity with Hypertension among Orthopaedic Patients in a Dar es Salaam Hospital: Identifying Missed Opportunities in Nursing Care (Tanzania Medical Journal, 2023)
BackgroundStudies on the prevalence of hypertension in Africa show that hypertension has become more prominent among the adult population. Nursing care of hospitalised orthopaedic patients, however, mainly focuses on the presenting condition. The presence of orthopaedic patients with comorbidities like hypertension in the wards, therefore, offers feasible opportunities for more holistic nursing care.Broad Objective To investigate gender differences in the prevalence and patterns of hypertension among orthopaedic patients in order to identify care gaps that point towards missed opportunities to benefit patients through holistic nursing care.MethodsA quantitative cross-sectional survey, stratified by gender, was used to investigate statistically how the prevalence and patterns of comorbidity with hypertension in six public orthopaedic wards varied by gender, age and type of admission (emergency versus cold cases). The data analysis used descriptive statistics, visual displays (boxplots and pie charts), contingency tables, and hypothesis testing for difference between proportions and means.ResultsA majority of male patients were emergency patients and younger in age; a majority of female patients, however, were cold cases and older. Prevalence of hypertension differed significantly between female (44.4%) and male (24.7%) patients. Undiagnosed and uncontrolled hypertensives accounted for 30.0% of female versus 20.4% of male patients. The majority of male hypertensives were undiagnosed; the majority of female hypertensives were diagnosed, but half of them were uncontrolled hypertensives. Only half of all diagnosed patients took medication. Prevalence of undiagnosed or uncontrolled hypertension persisted among re-admitted patients.Conclusions and RecommendationsUndiagnosed hypertensives, particularly younger and middle-aged male patients; uncontrolled and unmedicated diagnosed hypertensives, both male and female; and hypertensive patients discharged without clear information concerning their condition all are identified areas for improvement in nursing care. This article recommends that nursing care adopt a more proactive rather than reactive approach to hypertension care, to reduce the risk of health crises occurring due to comorbidity, of postponement of surgery due to high BP, and of discharging patients who remain undiagnosed or untreated for hypertension. It is also recommended to create greater awareness among patients at risk of hypertension about their condition.